INTERNALISASI FIQH MU‘AMALAH DALAM PEMBELAJARAN PAI UNTUK PENGUATAN ETIKA SOSIAL - Muhammad Nurin; Chanifudin (EL-TA’DIB: Journal of Islamic Education, 2025)
Fiqh mu‘amalah is an essential component of Islamic teachings that regulates social and economic relations based on the principles of justice, honesty, and moral responsibility. In the educational context, particularly in Islamic Religious Education (PAI) learning, fiqh mu‘amalah has strategic potential to shape students’ social ethics so that they are able to interact with dignity amid the dynamics of modern life. This article aims to examine the concept of internalizing fiqh mu‘amalah in PAI learning and its relevance to strengthening students’ social ethics. This study employs a qualitative approach using a library research method by analyzing literature on fiqh mu‘āmalah, Islamic education, and contemporary studies on social ethics. The findings indicate that the internalization of fiqh mu‘amalah values in PAI learning can be implemented through curriculum integration, contextual learning methods, and teachers’ role modeling. Values such as honesty, justice, trustworthiness, and social responsibility are highly relevant in strengthening students’ social ethics in their daily lives. Therefore, PAI learning that internalizes fiqh mu‘āmalah is not merely oriented toward cognitive mastery but also plays an effective role in shaping ethical social behavior grounded in Islamic values. Keywords: Fiqh mu‘amalah, Islamic Religious Education, value internalization, social ethics, Islamic education